Sphyraena arabiansis a new species of barracuda (Family: Sphyraenidae) from the south-west coast of India - Abdussamad, E. M.; Retheesh, T. B.; Thangaraja, R.; Bineesh, K. K; Prakashan, D. (Indian Journal of Fisheries, 2015)
A new species of barracuda Sphyraena arabiansis is described based on specimens collected from the eastern Arabian Sea off Kerala coast, India. The new species is morphologically similar to Sphyraena barracuda and both were so far considered as one species. Characters such as more and relatively small cycloid scales, 118-122 along lateral line, 11 along vertical axis above lateral line at first dorsal and 13 below the lateral line at anal origin; broad, round spoon shaped maxilla ending vertically below, before the anterior margin of the eye, narrow inter orbital area (4.2-5.13 in head length) and more prominent pointed paired central lobes of caudal fin make Sphyraena arabiansis sp. nov. clearly distinct from S. barracuda. Other distinguishing characters are prominent curve of the lateral line before the origin of first dorsal fin, absence of black spots on the body, white branchiostegal membrane, broad, thick and inwardly curved otoliths with round, blunt posterior end and an elongated, pointed anterior upper lobe. The mitochondrial Cytochrome oxidase C subunit 1 (COI) gene sequence studies revealed that the new species has distinct genetic divergence from S. barracuda and other species of the family occurring in the area.